Role of rare variants in undetermined multiple adenomatous polyposis and early-onset colorectal cancer - Lefevre, J; Bonilla, C; Colas, C; Winney, B; Johnstone, E; Tonks, S; Day, T; Hutnik, K; Boumertit, A; Soubrier, F; Midgley, R; Kerr, D; et al. (Nature Publishing Group, 2012)
Some 15-20% of multiple adenomatous polyposis have no genetic explanation and 20-30% of colorectal cancer (CRC) cases are thought to be due to inherited multifactorial causes. Accumulation of deleterious effects of low-frequency dominant and independently acting variants may be a partial explanation for such patients. The aim of this study was to type a selection of rare and low-frequency variants (<5%) to elucidate their role in CRC susceptibility. A total of 1181 subjects were included (866 controls; 315 cases). Cases comprised UK (n=184) and French (n=131) patients with MAP (n=187) or early-onset CRC (n=128). Seventy variants in 17 genes were examined in cases and controls. The effect of the variant effect on protein function was investigated in silico. Out of the 70 variants typed, 36 (51%) were tested for association. Twenty-one variants were rare (minor allele frequency (MAF) <1%). Four rare variants were found to have a significantly higher MAF in cases (EXO1-12, MLH1-1, CTNNB1-1 and BRCA2-37, P<0.05) than in controls. Pooling all rare variants with a MAF <0.5% showed an excess risk in cases (odds ratio=3.2; 95% confidence interval=1.1-9.5; P=0.04). Rare variants are important risk factors in CRC and, as such, should be systematically assayed alongside common variation in the search for the genetic basis of complex diseases.